Manual de funciones para el área administrativa del Colegio Nacional Mixto “13 de Octubre” – Calceta - Alcívar Chica, Cesar Vitaliano (2012)
The objective of this research was to elaborate a Functions Manual for the personnel in the Administrative Area at 13 de Octubre Secondary School for the optimization of work and activities in general. For this reason, it was necessary to diagnose the current administrative situation of the School. Through an interview carried out with questions like, “give details about your responsibilities in the school”, “do you consider the flowchart of functions to be well defined, why?”, “are your administrative duties in the school already defined?”, “In your daily activities what department do you specifically coordinate with?” With the results obtained, it was determined the necessity to implant the manual in order to describe responsibilities and obligations in a clear and precise way. In addition, the school will have a solid and organized structure when administrative functions are performed. The manual was elaborated as an instrument for the awareness among the administrative personnel, and it was designed in an easy format to facilitate its understanding and application along with the respective activities clearly described. Therefore, it should be implemented to improve the current situation at the institution.